Strong (001) facet-induced growth of multi-hierarchical tremella-like Sn-doped V2O5 for high-performance potassium-ion batteries. Issue 45 (5th November 2019) - Xing, Lidong; Yu, Qiyao; Bao, Yanping; Chu, Jianhua; Han, Kun; Chong, Shaokun; Lao, Cheng-Yen; Lai, Feili; Li, Ping; Xi, Kai; Wang, Wei (Alex)
Abstract : A tremella-like Sn-doped V2 O5 (denoted as SDVO) is prepared via a solvothermal method for high performance potassium-ion batteries (KIBs). SDVO can improve the electronic conductivity and enhance the capacity and cycle stability of KIBs. Abstract : Potassium-ion batteries (KIBs) are promising alternatives to lithium-ion batteries (LIBs) due to low-cost and abundant potassium resources. However, the large volume expansion and inevitable electrode pulverization during cycling are the urgent problems to be solved. Herein, the Sn element is introduced to form Sn-doped V2 O5 (denoted as SDVO) via partially replacing V with Sn. Strong (001) facet-induced growth promotes the conversion of V2 O5 from nanoparticles to nanosheets. The multi-hierarchical structure is composed of a primary mesoporous structure, secondary SDVO nanosheets and a tertiary three-dimensional (3D) tremella-like nanostructure. Notably, the 3D tremella-like nanostructure assembled from two-dimensional (2D) nanosheets can curb the volume expansion of V2 O5 . Furthermore, the tremella-like architecture with abundant mesopores and a large surface area can reduce the transmission path of K ions and increase the reaction active sites. First-principles calculations show that Sn doping can induce the preferred orientation of the (001) crystal facet in V2 O5 and improve the overall electronic conductivity of SDVO. Benefiting from these designed features, the SDVO composite with an optimized electrolyte exhibits a high capacity of 308 mA h g −1 at 0.1 A g −1 after 150 cycles and excellent cycle stability of 188 mA h g −1 even after 3000 cycles at 0.5 A g −1 .